2000
DOI: 10.1002/1526-968x(200005)27:1<22::aid-gene40>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal-epithelial transition in the developing metanephric kidney: Gene expression study by differential display

Abstract: The developing metanephric kidney is a convenient model to study molecular events associated with epithelial cell differentiation. To determine the genes involved in the defining event of this process, namely, the conversion of metanephric mesenchyme to the epithelium of the nephron, we applied differential display (DD) techniques. Explants of rat metanephric mesenchymes were induced to condense ex vivo with fibroblast growth factor 2 (FGF2) or to form tubules with FGF2 and conditioned medium (CM) from a cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 40 publications
(32 reference statements)
1
14
0
1
Order By: Relevance
“…Currently, information is limited regarding whether and how ER stress and UPR are involved in the renal development, but a previous report showed that expression of GRP78 is induced in developing metanephric kidneys [67]. Further investigation will be required to clarify developmental significance of this observation and to identify roles of UPR in the kidney development.…”
Section: Renal Developmentsupporting
confidence: 70%
“…Currently, information is limited regarding whether and how ER stress and UPR are involved in the renal development, but a previous report showed that expression of GRP78 is induced in developing metanephric kidneys [67]. Further investigation will be required to clarify developmental significance of this observation and to identify roles of UPR in the kidney development.…”
Section: Renal Developmentsupporting
confidence: 70%
“…One potential mechanism of this apparent protective effect could be the in utero resetting of the threshold for UPR activation: that is, a greater degree of ER stress would need to occur prior to the activation of the deleterious effects of the UPR. This hypothesis is supported by the work of Plisov et al (44), who demonstrated that GRP78 was expressed in the developing metanephros, most notably within the cortical glomeruli, collecting ducts, and Figure 10. Proposed mechanism of increased PAT dysfunction observed in obese NR offspring.…”
Section: Nutrient Restriction Appears To Protect the Renal Tissues Frmentioning
confidence: 58%
“…The transcription factors up-regulated in EMT are displayed in Table S3 together with their most frequent CREs . Underlined are four high CRE frequency transcription factors that were chosen for further study for their relevance to TGF-ÎČ-induced EMT ( Atf2 [48], [49], SP1 [50], [51], [52], Klf10 [53], [54], and Sox11 [55]). All four transcription factors are induced within 6 hours and remain up-regulated at 18 hours with two, Klf10 and Sox11 , being up-regulated throughout EMT.…”
Section: Resultsmentioning
confidence: 99%